Tradisi Hadiah Pernikahan Berbalut Hutang di Kalangan Masyarakat Kerinci Perspektif Islam - Yunara, Lutia (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
The act of giving and receiving gifts is a deeply rooted tradition in Islam, known to strengthen the bonds of Islamic brotherhood. In the region of Kerinci, this tradition takes the form of giving wedding gifts, either in the form of money or goods, as a contribution to the celebration. However, it is concerning that this tradition has transformed into a transaction resembling a debt, which goes against the core principles of Islamic teachings. This paper is dedicated to analyzing the practice of debt-wrapped wedding gifts within the Kerinci community, offering an Islamic perspective. The research employs a combination of field research and library study, using interviews and literature review as the primary methods of data collection. The informants involved in this research are individuals possessing knowledge and experience related to this tradition. The findings reveal that the practice of expecting recipients to return gifts of equal value contradicts Islamic principles, raising important ethical and moral considerations.